The Psychometric Properties of the Norwegian version of Aid to Capacity Evaluation (ACE) - Brøndbo, Per Håkan; Halvorsen, Marianne (PsykTestBarn, 2019)
Description: The Aid to Capacity Evaluation (ACE) is a semi structured decisional aid with the purpose to help clinicians to assess patients’ capacity to make treatment decisions. The scheme consists of seven relevant areas to consider. The interview takes 5-10 minutes. The Norwegian version was translated by Jørgen Dahlberg and Reidar Pedersen, Center of Medical Ethics, University of Oslo, in 2011. Literature search: The literature search, and contact with the translators, did not identify any relevant studies. Psychometric: There is no documentation about the psychometric properties of the ACE in a Scandinavian context. Conclusion: The psychometric properties of the ACE in a Scandinavian context are unknown. Before information about the psychometric properties of the ACE are available, clinical use should be conducted with great caution, especially if the scores are used as part of the decision basis on an individual level.